Spirituality in modern literature: Kahlil gibran and the spiritual quest - Altabaa, Homam (IIUM Press, International Islamic University Malaysia, 2017)
This study explores the various mystical aspects that encompass Gibran's creative works in English and Arabic. It presents an overview of theistic mysticism followed by an examination of the mystical themes represented by Gibran such as Truth, Perfect Divine Being, mystic path, and spiritual morality with analogies from Islamic and Christian mysticism. The study finds that Gibran adopted mysticism as a universal answer to questions about the meaning of life and as a path that seeks to elevate man into a world of spiritual and moral perfection. Gibran uses a prophetic voice to guide the soul from its transcendental origin through a journey of purification, gnosis, and love to reach mystical unity with God. The study shows that the mystical element is the link that unifies his Arabic and English works, and propels them to enduring literary and popular success across cultures. In this, he places himself as a writer in a traditional context of mysticism, taking the esoteric heart and spiritual core of all religions to be one. Additionally, the moral values promoted by Gibran are based on his mystical outlook and his conception of a just and loving God.